2005
DOI: 10.1002/eji.200526173
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of human anti-acetylcholine receptor monoclonal antibodies from transgenic mice expressing human immunoglobulin loci

Abstract: The isolation of human antibodies against muscle acetylcholine receptor (AChR), the autoantigen involved in myasthenia gravis (MG), is important for the development of therapeutically useful reagents. Monovalent antibody fragments from monoclonal antibodies against the main immunogenic region (MIR) of AChR protect the receptor from the destructive activity of MG autoantibodies. Human anti-AChR a-subunit antibody fragments with therapeutic potential have been isolated using phage display antibody libraries. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…On the day of the fusion the reciprocal titers were ϳ300. Titers of this magnitude are in keeping with those seen after immunization of BAB5 mice with other antigens (38), and moreover this final bleed was taken 3 days after the fifth booster was given, too early for detection of peak serum Ab titers. Other studies have suggested that MAbs can be readily isolated despite relatively weak serum Ab responses (55).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…On the day of the fusion the reciprocal titers were ϳ300. Titers of this magnitude are in keeping with those seen after immunization of BAB5 mice with other antigens (38), and moreover this final bleed was taken 3 days after the fifth booster was given, too early for detection of peak serum Ab titers. Other studies have suggested that MAbs can be readily isolated despite relatively weak serum Ab responses (55).…”
Section: Resultssupporting
confidence: 64%
“…Despite this and the lack of class switching from IgM to IgG in these mice, the IgM response underwent efficient affinity maturation as demonstrated by the derivation of the high-affinity MAbs N3C5 and N03B11. Prior studies using human Ig-producing transgenic mice have demonstrated their suitability for deriving MAbs against antigens such as human blood cells, tumor cell lines, haptens, the human acetylcholine receptor, and HIV-1 Env antigens (20,21,28,38,55). Interestingly, the immunization of the XMG2 XenoMouse strain with gp120 SF162 allowed the isolation of IgG2() MAbs that displayed neutralizing activity against the autologous primary isolate HIV-1 SF162 , FIG.…”
Section: Discussionmentioning
confidence: 99%
“…For the case of Mus musculus , sequences often can be associated to studies involving transgenic mice with human Ab loci. 32 36 …”
Section: Resultsmentioning
confidence: 99%
“…For the case of Mus musculus, sequences often can be associated to studies involving transgenic mice with human Ab loci. [32][33][34][35][36] A large number of low scoring human sequences are annotated with patents related to engineering and or animal Ab sources (US20050002930A1, JP2007524605A, EP2150565A2) often directed to human cancer and immune disorder treatments (JP2009221224A, EP2150565A2, WO2005063299A3, WO2004085474A2) like prostate cancer (WO0173032A2, JP2003528591A), or patents evolving in the vicinity of anti-human Abs (WO2005067477A3). Another possible explanation for the low scoring GenBank entries are their annotations designating them as unpublished or having incomplete publication records (e.g., GenBank IDs: EU620060, FW576479, DQ187727).…”
Section: Strategy To Reconstruct Nucleotide Sequences From Ab Amino Acid Sequencesmentioning
confidence: 99%
“…This is linked to a more effi cient B cell recovery and much reduced expression of endogenous λ L chain. Although human Igκ antibodies can be easily obtained from fi ve-feature mice, it may be an advantage to use individual four-feature strains, which either express human IgH,λ or human IgH,κ antibodies, to select the type of response Mendez et al 1997;Nicholson et al 1999;Magadán et al 2002;Protopapadakis et al 2005).…”
Section: Immune Responses and Affi Nity Of Human Igmentioning
confidence: 99%